Eyes on Customary Forests Transition of Traditional Forests into Production Forests - Wahyu RAMADAI, Eko; SALMA, Qorin Anida; Fitria CAHYANI, Adinda Agis (Indonesia Strategic Sustainability, 2024)
Forests as a medium for balancing nature are something whose importance cannot be ignored in human life and civilization. Forests must be managed, protected, and utilized sustainably for the community's welfare, both current and future generations. The problem of customary forests in Indonesia tends to be paradoxical; constitutionally, it has been regulated so that matters are aimed at providing justice, certainty and benefits for indigenous peoples and customary forests. However, Indonesia is known as